Use of Leaf Anatomy for Identification of Quercus L. Species Native to Kurdistan-Iraq. - Saleem E. Shahbaz; Shamiran S. Abdulrahman; Haliz A. Abdulrahman (Science Journal of University of Zakho, 2015)
Anatomical features of the leaves of Quercus L. species are presented in this study for the first time. Leaves are bifacial and the palisade parenchyma of Q. aegilops and Q. libani is stratified into two layers, of nearly equal width, while that of Q. infectoria and Q.macranthera composed of only one layer. The cortex of both midrib and petiole is well developed with collenchyma starting just beneath the epidermis. The collenchyma of Q. aegilops is extremly thick compared with that of other species. Vascular bundles of the midrib and petiole are completely enclosed by the two pericycle layers of fibers and sclerenchyma. While the number of vascular bundles and sclerenchyma groups cupping them is 3 and 2 for midribs of Q. aegilops and Q. libani respectively, the number turns into 2 vascular elements of different appearance in their petioles. Petiole secondary vascular bundles are well developed and their sclerenchyma groups more lignified in Q. infectoria but less developed and reduced in Q. macranthera. From the results, it is concluded that the leaf blade and petiole anatomical features can provide diagnostic characters for distinguishing Quercus species of Iraq. Results also strongly support placing Q. aegilops and Q. libani in the section Cerris but Q. infectoria is more reliable in the section Mesobalanus.